2018
DOI: 10.1038/s41467-018-03791-y
|View full text |Cite
|
Sign up to set email alerts
|

Conditional privatization of a public siderophore enables Pseudomonas aeruginosa to resist cheater invasion

Abstract: Understanding the mechanisms that promote cooperative behaviors of bacteria in their hosts is of great significance to clinical therapies. Environmental stress is generally believed to increase competition and reduce cooperation in bacteria. Here, we show that bacterial cooperation can in fact be maintained because of environmental stress. We show that Pseudomonas aeruginosa regulates the secretion of iron-scavenging siderophores in the presence of different environmental stresses, reserving this public good f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 52 publications
(53 reference statements)
3
60
1
Order By: Relevance
“…It required 30 times more pyoverdine to reach the maximum growth rate compared to 2.5 times in the other strains including ∆fpvB. The ability of different stressors including cadmium, violet light and the aminoglycosides tobramycin and gentamicin to increase the expression of some genes involved in pyoverdine and pyochelin (secondary iron chelator) synthesis even when iron is available has been described previously [21,22,[30][31][32] but the precise mechanism by which this takes place is unknown. Our results offer insights into the properties of the secondary receptor: supplementing with pyoverdine supports that growth at the expense of FpvB was suboptimal, likely due to a lower efficiency in pyoverdine uptake via FpvB -both receptors share a 54% amino acid sequence similarity (38% identity) - [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…It required 30 times more pyoverdine to reach the maximum growth rate compared to 2.5 times in the other strains including ∆fpvB. The ability of different stressors including cadmium, violet light and the aminoglycosides tobramycin and gentamicin to increase the expression of some genes involved in pyoverdine and pyochelin (secondary iron chelator) synthesis even when iron is available has been described previously [21,22,[30][31][32] but the precise mechanism by which this takes place is unknown. Our results offer insights into the properties of the secondary receptor: supplementing with pyoverdine supports that growth at the expense of FpvB was suboptimal, likely due to a lower efficiency in pyoverdine uptake via FpvB -both receptors share a 54% amino acid sequence similarity (38% identity) - [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…A particularity of this system is that the social process is mediated by a diffusible antiviral protein. Therefore, IFN acts in a manner opposed to classical public goods such as secreted enzymes2022. Suppressing IFN secretion creates a space favorable to viral growth, analogous to preventing the release of a pollutant.…”
Section: Theorymentioning
confidence: 99%
“…In a previous study, cheaters could help to counteract competition among microorganisms and foster biodiversity in well-mixed media by invading the community of cooperating siderophore producers ( Leinweber et al, 2017 ). However, another study indicated that cheaters could be resisted by the conditional privatization strategy under stressful conditions ( Jin et al, 2018 ). Therefore, it might be important to investigate the behavior pattern of uncooperative organisms in systems.…”
Section: Introductionmentioning
confidence: 99%